2017
DOI: 10.1093/annonc/mdw661
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of second tumors after treatment with or without radiation for rectal cancer

Abstract: Patients with previous rectal cancer had a marginally increased risk of a second tumor compared with the general population. Gynecological tumors occurred more often in females who received RT, but this did not result in an overall increased risk for a second cancer. RT even seemed to have a protective effect on the development of other second pelvic tumors, pre-dominantly for prostate cancer. These findings are highly important and can contribute to improved patient counseling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 25 publications
3
33
0
Order By: Relevance
“…This was the first large Asian general population-based study, which is in concordance with the results of a previous SEER data-based study [11] or previous Netherlands population-based cancer registry [13]. Competing risk regression model adjusted for death was used in our study to show a decreasing risk of prostate cancer after radiation therapy, compared with no radiation therapy in the rectal cancer patients group.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This was the first large Asian general population-based study, which is in concordance with the results of a previous SEER data-based study [11] or previous Netherlands population-based cancer registry [13]. Competing risk regression model adjusted for death was used in our study to show a decreasing risk of prostate cancer after radiation therapy, compared with no radiation therapy in the rectal cancer patients group.…”
Section: Discussionsupporting
confidence: 85%
“…Although the results showed that the potential prostate cancer risk from radiotherapy was small [10], a long-term risk in rectal cancer survivors should not be overlooked. In last year, two articles related to this topic were published, all with the same results of protection of prostate cancer incidence [12,13]. In this study, we recruited a nationally representative cohort of rectal cancer patients to investigate whether rectal cancer patients who received radiotherapy are at a greater risk of prostate cancer after a maximum of 13 years of follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…The reduction of prostate cancers was confirmed in other studies, but they also found an increased risk for some gynaecological cancers. [214][215][216] The latter study, also found an increased risk for lung cancer and lymphoma in irradiated patients. 216 Effect on distant failure?…”
Section: Toxicity From Radiotherapymentioning
confidence: 73%
“…Our proposed nomogram could be useful for calculating the 3‐year, 5‐year, and 10‐year probabilities of developing an SPM in the presence of competing causes of death. Unlike most prior studies that have assessed the overall risk of developing an SPM among cancer survivors from an overall perspective , our study focused on the prediction from a more accurate perspective. Patients’ risk of SPMs can be estimated if their characteristics are given.…”
Section: Discussionmentioning
confidence: 99%